Phylogenetic Analysis and Antibiotics Resistance of Listeria Monocytogenes Contaminating Chicken Meat in Surabaya, Indonesia - Eduardus Bimo Aksono; Katty Hendriana Priscilla Riwu; A. T. Soelih Estoepangestie; Herinda Pertiwi (Veterinary Medicine International)
The objective of this study was to identify the phylogenetic analysis and antibiotic resistance of Listeria monocytogenes contaminating chicken meat in Surabaya. 60 chicken meat samples were collected from supermarkets, mobile vendors, and traditional markets in Surabaya. A selective medium is used for isolation and identification of Listeria monocytogenes by chopping 25 grams of the chicken meat and to put it into the sterilized Erlenmeyer flasks. Some methods were used for the identification procedures, such as biochemical and morphological tests, antibiotic resistance test, PCR, and sequencing; also a phylogenetic analysis was conducted by a neighbor-joining analysis using Genetix Mac ver 8.0 with hlyA genes of Listeria monocytogenes recorded in GenBank, such as Lineage I (KC808543), Lineage II (AY229462, AY229346, AY229499, and AY229404), Lineage III (KJ504139, HQ686043, KJ504116, and DQ988349), and Lineage IV (EU840690, EF030606). The result shows that the prevalence of L. monocytogenes in Surabaya contaminating the chicken meat samples from the supermarkets was 10% (2/20), from the mobile vendors was 0/20 (0%), and from the traditional markets was 5% (1/20). It was seen from the band at 456 bp fragment. Furthermore, three isolates found in Surabaya were included in the new lineages which were resistant to old-generation antibiotics such as sulfamethonazole-trimetophrim (SXT) and amoxyllin sulbactam (MAS), but they were still sensitive to new-generation antibiotics such as cefotaxime (CTX) and meropenem (MEM).